2020
DOI: 10.3390/ijms21176383
|View full text |Cite
|
Sign up to set email alerts
|

USP14 Regulates DNA Damage Response and Is a Target for Radiosensitization in Non-Small Cell Lung Cancer

Abstract: Non-small cell lung cancer (NSCLC) represents ~85% of the lung cancer cases. Despite recent advances in NSCLC treatment, the five-year survival rate is still around 23%. Radiotherapy is indicated in the treatment of both early and advanced stage NSCLC; however, treatment response in patients is heterogeneous. Thus, identification of new and more effective treatment combinations is warranted. We have identified Ubiquitin-specific protease 14 (USP14) s a regulator of major double-strand break (DSB) repair pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…et al, 2019 ; Xu et al, 2020 ). The IC 50 of IU1 is 4.7 μM 5 , and concentrations of 50–100 μM IU1 have been used in multiple cancer cells ( Li H. et al, 2019 ; Xia et al, 2019 ; Sharma et al, 2020 ; Sharma and Almasan, 2020 ). We found that the viability of AGS and MKN-28 cells was remarkably suppressed by 75–100 μM IU1, while not in BGC-823 cells ( Figure 6J ).…”
Section: Resultsmentioning
confidence: 99%
“…et al, 2019 ; Xu et al, 2020 ). The IC 50 of IU1 is 4.7 μM 5 , and concentrations of 50–100 μM IU1 have been used in multiple cancer cells ( Li H. et al, 2019 ; Xia et al, 2019 ; Sharma et al, 2020 ; Sharma and Almasan, 2020 ). We found that the viability of AGS and MKN-28 cells was remarkably suppressed by 75–100 μM IU1, while not in BGC-823 cells ( Figure 6J ).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro and in vivo studies have shown that genetic and pharmacological inhibition of USP14 induces degradation of an androgen receptor (AR), favoring tumor suppression in AR-positive breast cancer cells or prostate cancer cells ( Liao et al, 2017 ; Liao et al, 2018 ). USP14 promotes tumor growth by regulating DNA damage response or ER stress-mediated autophagy in non-small cell lung cancer cells ( Moghadami et al, 2020 ; Sharma and Almasan, 2020 ). Alone this line, several compounds targeting UCHL5 and USP14 have been developed, including b-AP15 ( D'Arcy et al, 2011 ), VLX1570 (b-AP15 analog) ( Wang et al, 2016 ), AC17 (curcumin analog) ( Zhou et al, 2013 ), and various metal-based complexes ( Liu et al, 2014b ; Chen et al, 2018a ; Li et al, 2019a ).…”
Section: Targeting Dubs: a Novel Strategy For Cancer Therapymentioning
confidence: 99%
“…DNA damage is one of the major causes of radioresistance in lung cancer [ 153 ]. Ubiquitin-specific protease 14 (USP14) acts as a regulator [ 154 ] in double strand breaks (DSBs), which affects both non-homologous end-joining (NHEJ) and HR [ 155 , 156 ]. Knocking down USP14 by using short hairpin RNA (shRNA) showed a notable increase in the radiosensitivity of NSCLCs [ 154 ].…”
Section: Mechanism Of Radiotherapy Resistance In Lung Cancermentioning
confidence: 99%